Optimization of Water Content for the Cryopreservation Of Allium sativum In Vitro Cultures by Encapsulation-Dehydration - Lynch, P T; Souch, G R; Zamecnik, J; Harding, K (Cryo letters, 2016)
BACKGROUND: There is a general requirement to determine and correlate water content to viability for the standardization of conservation protocols to facilitate effective cryostorage of plant germplasm. OBJECTIVE: This study examined water content as a critical factor to optimize the cryostorage of Allium sativum. MATERIALS AND METHODS: Stem discs were excised from post-harvest, stored bulbs prior to cryopreservation by encapsulation-dehydration and water content was determined gravimetrically. RESULTS: Survival of cryopreserved stem discs was 42.5 %, with 22.5 % exhibiting shoot regrowth following 6 h desiccation. Gravimetric data demonstrated a correlation between water content corresponding with survival / regrowth from desiccated, cryopreserved stem discs. For encapsulated stem discs a 25 % residual moisture and corresponding water content of 0.36 g H2O g-1 d.wt correlated with maximal survival following ~6.5 h of desiccation. CONCLUSION: The data concurs with the literature suggesting the formation of a stable vitrified state and a 'window' for optimal survival and regrowth that is between 6 - 10 h desiccation. Further studies using differential scanning calorimetry (DSC) are suggested to substantiate these findings.
Keywords: Water; Plant Roots; kryoprezervace; kořeny rostlin; česnek; Garlic; vitrifikace; Vitrification; vysoušení; Desiccation; Cryopreservation; voda